Anatomy Variation of Ruptured Anterior Communicating Artery (AcoA) Aneurysm : Serial Cases - Irsyad, Muhammad Ari; Nasution, Iskandar; Tala, Muhammad Ihsan Zulkarnain (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2020)
Introduction : Intracranial aneurysms (IA) is an acquired disease characterized by dilatation of intracranial arteries, and is usually found at the location of arterial branches in the cranii base region. The selection of management and anatomic variations is quite interesting to be discussed in the case of aneurysms. Cases Report : Four cases of AcoA aneurysm were reported with variations in clinical manifestations, A1 segment anatomy, fundal projections and management considerations (Coiling vs. Clipping). This case series illustrates the compatibility with previous case studies that have existed. Discussion : The author concludes that the actions taken in cases I, II and III are in the form of coiling due to age, dome and neck ratio and access to perform such difficult surgical procedures. In case IV , it was considered to be performed surgical clipping action due to the presence of intracerebal hemoraghic, and the approach can be done from a non dominant hemisphere, proximal control only through the right carotid and the location of the posterior dome which was favorable for surgical clipping Conclusion : Aneurysms from the ACA-anterior communicating artery (ACoA) complex are some of the most complex lesions in the field of vascular neurosurgery. This location is where most rupture aneurysms occured with high mortalities due to complications of vasospasm and SAH. The choice of management in aneurysm cases which involved many factors such as age and anatomic variations.